Comparative evaluation of effectiveness of manual and various rotary retreatment techniques for removal of root canal filling material: An in-vitro study - Jagtap, Apoorva; Aher, Gayatri; Gulve, Meenal; Kolhe, Swapnil (Endodontology : journal of Indian Endodontic Society, 2022)
Aim: This study intended to compare the effectiveness of manual files H-files and ProTaper universal retreatment (PTUR), R-Endo retreatment, and gutta-percha removal (GPR) Mani retreatment rotary files for removing root canal filling material. Materials and Methods: Eighty mandibular premolars with single canal were selected. The canals were enlarged with ProTaper rotary files up to F2 and obturated using the lateral condensation technique. Then, the samples were randomly divided into four groups and retreated using hand files and rotary retreatment files. The area of remaining root canal filling material was evaluated by splitting the tooth using a stereomicroscope with ×10 and auto computer-aided design software and the percentage of remaining filling material on canal walls was calculated with equation: area % of remaining filling material = area of remaining material ×100/area of canal. One-way ANOVA was carried out to compare the groups and post hoc Tukey's test for pairwise association with each of four groups. Results: Group A (H-files) showed 61.87% of remaining filling material, Group B (PTUR) showed 24.94%, Group C (R-Endo) showed 37.12%, and Group D (GPR Mani) showed 45.95% of remaining root canal filling material. Conclusions: All the groups showed residual root canal filling material. Least was seen in group retreated using PTUR files and maximum was seen in group retreated with H-files.